Graphene nanoscroll/nanosheet aerogels with confined SnS 2 nanosheets : simultaneous wrapping and bridging for high-performance lithium-ion battery anodes - Zhang, Youfang (2018)
In this paper, we report graphene nanoscrolls bridged by crumpled graphene nanosheets as an effective conductive framework for confining SnS2 nanosheets for lithium-ion battery (LIB) applications. The nanoscroll/nanosheet hybrid aerogels (GNAs) with confined SnS2 nanosheets are facilely prepared via fast quenching, freeze-drying and thermal annealing. During quenching, wrapping SnS2 nanosheets in the nanoscrolls and bridging the one-dimensional nanoscrolls by the two-dimensional nanosheets occur simultaneously, and the ratio of nanoscrolls/nanosheets can be controlled by simply adjusting quenching conditions. The optimized SnS2/GNA is highly porous with a large specific surface area of 127.1 m2 g−1 and multi-scale pore structure, which can effectively prevent SnS2 aggregation to provide abundant lithiation/delithiation sites, and buffer volumetric change and pulverization of SnS2 nanosheets. Moreover, the three-dimensional conductive network formed in the hybrid aerogels can remarkably improve its electrical conductivity while providing sufficient channels for the transportation of lithium ions and charges. As a result, the optimized SnS2/GNA nanocomposite exhibits enhanced electrochemical performance with a high initial reversible capacity (1514.8 mAh g−1 at 0.1 A g−1), excellent rate capacity (665.4 mAh g−1 at 5 A g−1) and good cyclic stability (1050 mA h g-1 at the 50th cycle). This may provide an efficient generic approach for encapsulation of transition metal dichalcogenide materials in conductive nano/micro confined spaces for fabrication of high-performance LIB anodes.